2021
DOI: 10.1016/j.jbc.2021.100904
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial metabolism regulates macrophage biology

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 117 publications
(112 reference statements)
5
104
0
1
Order By: Relevance
“…IRG1 was found as the most upregulated protein detected by both CAT-Prox and immunoblotting, indicating the high fidelity of CAT-Proxbased proteomics (Figure 3g). Noteworthy, Aco2 (aconitase 2) and IRG1 (aconitate decarboxylase 1) were responsible for itaconate production in a tandem manner, 28 agreeing with the previous discovery of enhanced itaconate production in LPSstimulated macrophages. 29,30 Similarly, the increase of reactive electrophile species 29,30 was likely due to the upregulation of Acadsb.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…IRG1 was found as the most upregulated protein detected by both CAT-Prox and immunoblotting, indicating the high fidelity of CAT-Proxbased proteomics (Figure 3g). Noteworthy, Aco2 (aconitase 2) and IRG1 (aconitate decarboxylase 1) were responsible for itaconate production in a tandem manner, 28 agreeing with the previous discovery of enhanced itaconate production in LPSstimulated macrophages. 29,30 Similarly, the increase of reactive electrophile species 29,30 was likely due to the upregulation of Acadsb.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…Mitochondria are also key for energy metabolism in macrophages and the regulation of macrophage biology [ 55 , 56 ]. For instance, M1-like macrophages are characterized by increased glycolytic metabolism, production of pro-inflammatory mediators (e.g., ROS, IL-6), and mitochondria fragmentation (fission), while M2-like macrophages display increased FAO and release of anti-inflammatory cytokines, as well as mitochondria elongation/fusion [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The changes of mitochondrial dynamics between fusion and fission play an important role in macrophage function [ 40 , 41 ] and previous studies demonstrated that DRP1-dependent mitochondrial fission could induce the pro-inflammatory activation of macrophages [ 20 ]. In this study, mitochondrial fission and the pro-inflammatory response induced by STING activation were all inhibited by transfection of DRP1 shRNA in LPS-treated KCs, indicating that DRP1-mediated mitochondrial fission was required for STING signaling activation.…”
Section: Discussionmentioning
confidence: 99%